Optimisasi Robust pada Masalah Pickup dan Delivery dengan Ketakpastian Time Window - Dewi, Belinda Eka Sarah (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2024)
The pickup and delivery problem with time window (PDPTW) is a problem related to planning the optimal route for a vehicle in providing transportation services to a number of customers with the aim of minimizing operational costs. The classic PDPTW model generally assumes that parameter values are certain. However, in practice it is difficult to find the exact value of a parameter. Time window uncertainty is often found in the pickup and delivery problem by transportation service providers. This is important for transportation service providers, because taking into account the uncertainty of the time window is expected to result in better travel routes. In this paper, a deterministic model of PDPTW was developed. Robust Optimization is used to solve the time window uncertainty. The time window uncertainty is assumed to be in a box uncertainty set. Furthermore, Robust counterpart model is developed which is computationally tractable using Linear Programming.